Hypoglycaemia on an oral glucose tolerance test in pregnancy – Is it clinically significant?. (January 2019) - Yuen, Lili; Bontempo, Sara; Wong, Vincent W.; Russell, Hamish
Abstract: Aim: During pregnancy, some women have a low glucose level on the 75 g oral glucose tolerance test (OGTT). The implications of this are unclear and there is no guideline on how to manage these women. Method: We recruited pregnant women with a glucose level <3.5 mmol/L at 1- or 2-h during a screening antenatal OGTT. These women (Group 1) underwent self-monitoring of blood glucose (SMBG) over a two-week period. We also compared Group 1′s demographic and pregnancy outcomes data with women who had normal OGTT results (Group 2) and women diagnosed with gestational diabetes mellitus (GDM) (Group 3). Results: 52 women were recruited. Post-hoc analysis of the SMBG results revealed 50% of women experienced 2 or more elevated fasting BGLs (>5.1 mmol/L) in a week when using the Australian Diabetes in Pregnancy Society (ADIPS) criteria. A further 8% women had elevated 2-h glucose levels (above 6.7 mmol/L). Group 1 women tended to have higher booking weight. They were less likely to have a history of macrosomia or be of East or South-East Asian ethnicity. There were no differences in pregnancy outcomes between Groups 1 and 2, but Group 1 had a higher rate of congenital abnormality (6%) than Group 3 (2%). Conclusion: A large proportion of pregnant women who had a low glucose level on OGTT had elevated glucose levels on SMBG, however their pregnancy outcomes were not significantly different to women who had a normal OGTT. Currently there is not enough evidence to advocate routine SMBG and treatment for this group of women.